Sustainable Marketing Practices in the Indian FMCG Sector: SLR and Insights from Consumer Behaviour (2015-2025) - Hong, Yeoh Weng; Teck, Tan Seng; Sonar, Pradeep Ramesh; Tali, Altaf (International Review of Management and Marketing, 2026)
The current statistics reveal that the Fast-Moving Consumer Goods (FMCG) sector contributes approximately to the range of 211 billion to 245 billion yielding 3% to 10% of India’s GDP. It is expected to grow exponentially over the next five years to capture the overall market size as high as 1.28 trillion. The present study of PRISMA-guided systematic literature review synthesises 70 peer-reviewed articles published between 2015 and 2025 in Q1/Q2 Scopus/ABDC-ranked journals, having contextual and empirical depth. The review unleashes that green promotion (average β = 0.23) is by far the strongest driver of green buying behaviour among the consuming segment in India, followed by place (β = 0.21) and product (β = 0.17), while the price remains largely insignificant (β = 0.04). The overall awareness (r = 0.537) and concern (r = 0.451) together explain 58 % of actual green purchase intention. Demographically females (60.25 % of aggregated samples) and mid-income consumers exhibit relatively stronger responses to promotion and product cues. Persistent barriers include greenwashing (42 % of claims perceived as non-verifiable), price sensitivity (35.8 %), and a blunt attitude-behaviour gap (95 % express pro-environmental attitudes). The review advances theory by proposing an original moderated-mediation framework tailored to Indian multi-cultural consumer groups constrained by socio-economic conditions, and projects towards an emphatic sustainable marketing scenario that drives green products to 25 % of FMCG sales by 2030.